Evaluation of Subendometrial and Intramyometrial Blood Flow after Intravenous Tranexamic Acid for Prevention of Postpartum Hemorrhage in Vaginal Delivery: A Randomized Controlled Study - Alaa M Ismail; Ahmed M Abbas; Mohamed A Shahat; Mohammed K Ali (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Objective: The study aims to test the effect of tranexamic acid (TA) on uterine vasculature and blood loss after vaginal delivery.  Materials and methods: A randomized, double-blind, placebo-controlled trial, conducted in Assiut Woman's Health Hospital, Egypt between the 1st of October 2015 and the 31st of March 2016 included pregnant women (37-42 weeks) with a single living cephalic fetus. The eligible women were randomized to receive TA or placebo after vaginal delivery. Doppler indices were measured for the subendometrial, intramyometrial and uterine blood vessels two hours after delivery. The main study outcome was the effect of TA on subendometrial and intramyometrial blood fl ow.  Results: Two hundred women were enrolled (n=100 in each group). There was a significant increase in the Doppler indices of subendometrial and intramyometrial blood vessels with no difference in indices in uterine arteries between both groups. The mean of estimated blood loss decreased significantly in TA group (p<0.001). The haematocrit and hemoglobin levels were higher in TA group than the placebo group after delivery (p<0.001).  Conclusions: The use of intravenous TA after vaginal delivery increases the resistance in the subendometrial and intramyometrial blood vessels and reduces postpartum hemorrhage.